Some Problems of Simultaneous Approximation of Functions of Two Variables and Their Derivatives by Interpolation Bilinear Splines - Vakarchuk, S. B.; Myskin, K. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
Exact estimates for the errors of approximation of functions of two variables and their derivatives by interpolation bilinear splines are obtained on certain classes.